PENGAWASAN TERHADAP USAHA BIDANG PERIKANAN OLEH PEMERINTAH DAERAH KABUPATEN KAMPAR TAHUN 2011-2012 - Wahyu, Rian; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
With the potential of the river through the Kampar of Kampar district, artificial reservoirs and some areas where the land is suitable for development of freshwater aquaculture has become the lifeblood of the district for the development of freshwater aquaculture Riau province have been used as minapolitan by the district directorate of aquaculture . The authors are interested in examining the government control of fishing effort in Kampar district. This study aims to determine the implementation of the monitoring conducted by the Department of Fisheries Kampar and the factors that affect the implementation of the surveillance . Control theory is the rationale in this study . The method used in this research is descriptive metoe analysis with qualitative approach that seeks to analyze the problems that arise in the field and tried to describe as clearly as possible. In the process of monitoring conducted by the Department of Fisheries Kampar district , there are some problems that occur due to oversight that does not work as expected , the problem is where the entrepreneur fish do not get effective coaching and also the lack of funding for entrepreneurs capitalize fish so that the fish businessmen sufficiently constrained to grow their businesses .This research was conducted in Kampar district Particularly in Reservoir Hydroelectric Koto Panjangsubdistrict XIII Koto Kampar , which is the key informants in this study is the Head of Department and Secretary of the Department of Fisheries , Sub Line of Business and Data , Business Sector Sub Fisheries Department of Fisheries , Head XIII Koto Kampar , Tanjung Alai village head , village head Merangin , Entrepreneur fish in hydroelectric reservoirs Koto Panjang , and community leaders .From the results of this study concluded that the lack of effective and weak supervision conducted by the Department of Fisheries Kampar district against businessman fish in reservoirs Hydroelectric Koto Panjangsubdistrict XIII Koto Kampar.Keywords : Expectation , Allocation , Performance Monitoring , and Corection Action.